Pengaruh Brand Equity Dan Kualitas Produk Terhadap Keputusan Pembelian Laptop Merek Asus di Kota Tabanan - Diarta, I Made Sukma; Suarmanayasa, I Nengah (Universitas Pendidikan Ganesha, 2021)
This study aims to examine the effect of brand equity and product quality simultaneously and partially on purchasing decisions. The research design used is quantitative causal. The subject of this research is the consumer of Asus laptop in Tabanan city and the object of research is brand equity, product quality and purchasing decision. Data were collected using a questionnaire method with multiple linear regression analysis. The results showed that (1) brand equity and product quality had a significant effect on purchasing decisions by 69.2%, (2) brand equity had a positive and significant effect on purchasing decisions by 31.3%, (3) product quality had a positive and significant effect. to the purchasing decision of 31.5%.